“It was a Shock to the Whole Family”: Challenges of Ukrainian Families Raising a Child with Autism - Semigina, Tetyana; Stoliaryk, Olha (Socialinė teorija, empirija, politika ir praktika, 2021)
Based on the family-centered approach and a consumer perspective this research examines the overall level of satisfaction with educational and social services of the families raising children with autism or autism spectrum disorders (ASD) in Lviv (Ukraine) and the challenges in interactions of such families with services. The survey (90 parents who are social work clients) and individual semi-structured interviews (30 parents) were used.The findings indicate the respondents’ evaluation of the services they receive and inclusive education could not be qualified as favorable. Key challenges identified within the study are: problems of staff preparedness and lack of information about services; personal feelings of emotional burnout; unrealistic expectations from services; social stigma related to autism and social isolation of parents raising a child with ASD.It is important for social workers to consider the need to collaboratively create the so-called social routers for families raising children with developmental disabilities during the early stages of family work. Verified information may reduce the parents’ stress and consolidate their efforts, help to avoid dubious treatments that are detrimental to the child’s health and are a significant financial burden to the family.
Keywords: family consumer perspective; access to service; autism; inclusive education; rehabilitation